MALAYSIA’S ISLAMIC TOURISM ENGAGEMENT WITH THE GULF COOPERATION COUNCIL (GCC) NATIONS - Ismail, Norafidah; Wahid, Ratnaria; Nanaa, Alhussein (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
Arab travellers hold significant influence over the Malaysian tourism industry, demonstrated by increasing arrivals (27,000 in 2017 to 33,000 in 2018) and a remarkable economic contribution of RM3.8 billion in 2018. Visitors from Saudi Arabia, followed by the UAE, Oman, Iran, and Kuwait, were identified as the leading spenders. Despite ambitious goals, such as drawing 30 million tourists for the 2020 Visit Malaysia campaign, the COVID-19 pandemic severely impacted the sector. In 2020, Malaysia experienced a staggering loss of 32 billion, as arrivals plummeted to 4.3 million from 26.1 million in 2019. In response to this challenging environment, Malaysia has enhanced its promotional efforts to specifically draw in Middle Eastern tourists, particularly those from Gulf states. Officials and travel agents are actively showcasing Malaysia’s attractions to entice potential visitors. A core strategy involves positioning Malaysia as a welcoming destination for Muslim travellers by promoting Islamic tourism, which is recognised as an emerging business niche with limitless possibilities. This article explores the specific rationale behind promoting Islamic tourism to the GCC. It further examines both the strategies currently implemented and those that warrant consideration to effectively attract GCC nations through the Islamic tourism framework.